EFFECT OF MAGNETIC FIELD ON THE CATALYTIC DECOMPOSITION OF H2O2 BY Fe3O4 - Tapia-Huanambal, N. (1999)
The decomposition of hydrogen peroxide H2O2, is a simple reaction to study the effect of the magnetic field in chemical reactivity. Hydrogen peroxide when dissolved in water is decomposed into oxygen and water slowly. In the absence of a catalyst, the reaction is extremely slow. We have studied the effect of the magnetic field in the synthesis of Fe3O4 and catalytic decomposition of H2O2 by Fe3O4 also propose a theoretical treatment of the magnetic field effect on chemical reactions. The results show that magnetite, synthesized within the magnetic field is more reactive than the synthesized outside the magnetic field.